Simultaneous ABO-incompatible living-donor liver transplantation and splenectomy without plasma exchange in China: Two case reports. (December 2017) - Chen, Guoyong; Sun, Janjun; Wei, Sidong; Chen, Yongfeng; Tang, Gaofeng; Xie, Zhantao; Xu, Huaen; Chen, Janbin; Zhao, Huibo; Yuan, Zhenhua; Wang, Weiwei; Liu, Guangbo; et al.
ABO-incompatible (ABO-i) living-donor liver transplantation (LDLT) is performed if an ABO-compatible graft cannot be obtained. However, a perfect desensitization protocol has not been established worldwide, especially for simultaneous ABO-i LDLT and splenectomy. We herein report two cases of ABO-i LDLT. To the best of our knowledge, this is the first case report of ABO-i LDLT in an adult patient in China. Splenectomy and T-cell-targeted immunosuppression (basiliximab) was used to overcome the blood group barrier in these recipients. The patients had good graft function without signs of antibody-mediated rejection throughout the 12-month follow-up. Thus, ABO-i LDLT with splenectomy is undoubtedly life-saving when an ABO-compatible graft cannot be obtained for patients in critical condition.